2019
DOI: 10.3897/bdj.7.e46833
|View full text |Cite
|
Sign up to set email alerts
|

From marine park to future genomic observatory? Enhancing marine biodiversity assessments using a biocode approach

et al.

Abstract: Few tropical marine sites have been thoroughly characterised for their animal species, even though they constitute the largest proportion of multicellular diversity. A number of focused biodiversity sampling programmes have amassed immense collections to address this shortfall, but obstacles remain due to the lack of identification tools and large proportion of undescribed species globally. These problems can be partially addressed with DNA barcodes (“biocodes”), which have the potential to facilitate the esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 130 publications
2
33
0
1
Order By: Relevance
“…MOTUs) had the highest identification success to 345 species-level, followed by Arthropoda (5 MOTUs;Figure 2). A similar pattern of 346 identification success was noted previously byIp et al (2019).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…MOTUs) had the highest identification success to 345 species-level, followed by Arthropoda (5 MOTUs;Figure 2). A similar pattern of 346 identification success was noted previously byIp et al (2019).…”
supporting
confidence: 83%
“…This was possible through the careful application of the 415 appropriate mitochondrial genetic code in the error-correction step. Our amplification and 416 identification success rates were similar to a previous barcoding study by Ip et al (2019), 417 which employed a combination of Sanger and Illumina barcoding, further suggesting that 418 MinION barcodes are viable and that performance success is defined more by primer choice 419 rather than sequencing platform. 420…”
Section: Minion Barcodes Are Viable 394supporting
confidence: 71%
See 1 more Smart Citation
“…A primer pair targeting exactly this same region, but using instead LoboR1 (Lobo et al 2013(Lobo et al , 2017 has been shown to produce similar or higher taxa recovery (e.g. Haenel et al 2017, Ip et al 2019, Chang et al 2020, but it has not been tested yet in NIS-focused studies.…”
Section: Marker Loci and Primer Pairsmentioning
confidence: 99%
“…We first trialed the BentoLab processes ex situ using samples that were routinely obtained from various intertidal and subtidal surveys. These collections were part of an ongoing effort to document the marine fauna in Singapore as well as to grow the local biodiversity knowledge base and barcode databases [ 38 , 39 ]. We then brought the sequencing setup out to the field and performed the entire sample-to-sequence workflow out at sea to demonstrate its utility.…”
Section: Introductionmentioning
confidence: 99%